Comparison of Platelet Count Assessment: Automated Haematology Analyzer Versus Manual Peripheral Blood Smear Examination in Thrombocytopenic Patients - Prashanth R; Elizabeth Shaji; Sandra (Annals of Pathology and Laboratory Medicine, 2026)
Background: Accurate platelet enumeration is critical in thrombocytopenia. Automated haematology analyzers provide rapid, reproducible counts but may be affected by platelet clumping, giant platelets, or abnormal platelet distribution. Manual peripheral blood smear (PBS) examination remains essential laboratory practice in assessment of severe thrombocytopenia and analyser-flagged cases.Methods: This prospective analytical study was conducted in the Haematology section of the Central Diagnostic Laboratory, Father Muller Medical College Hospital, over six months. A total of 140 thrombocytopenic samples (platelet count